On Prophets, Warriors, and Kings (De Gruyter, 2016)
While recent decades have seen a plethora of studies exploring the complex processes that shaped biblical books traditionally designated as Prophets, much remains to be done in order to uncover the rich history of their interpretation throughout the ages. This collection of essays aims at filling this gap by exploring different aspects of the exegesis of the Former and Latter Prophets in contexts both ancient and modern, Jewish and Christian. From the inner-biblical interpretation of the Prophets to the Dead Sea Scrolls, Apocrypha and Pseudepigrapha, the New Testament, Patristic writings, and contemporary rhetoric, this volume sheds light on how key figures in those books were read and understood by both ancient and not so-ancient readers
10.1515/9783110377385
Keywords: Electronic books; Judges; Kings; Könige; Propheten; Prophets; Richter; Samuel; Frühchristentum; Rezeption; Frühjudentum; Literatur; RELIGION / General